Development of a Game Model based on Manipulative Skills in Volleyball Games for Class VII Junior High School Students - Alfiana Alfiana; Selvi Atesya Kesumawati; Noviria Sukmawati; Selvi Melianty (UNIB Press, 2024)
Volleyball is one of the sports in PJOK learning. In class VII students' PJOK learning, the existing basic volleyball techniques of up and down passing have not been varied, so a game model based on manipulative skills has been created. Apart from playing, the manipulative skill-based game model also aims to provide education and other experiences according to age development and needs. The aim of this research is to develop a game model based on manipulative skills that can improve volleyball top and bottom passing for class VII junior high school students. Model development stage in research What is carried out is the analysis, design, development, implementation and evaluation (ADDIE) stages. The small group sample in this research was 25 people, while the large group sample was 60 people and also involved 3 teachers as respondents. The instrument used in this research was a questionnaire. Research results using expert validation tests Content Validity Index (CVI) and Content Validity Ratio (CVR) in the game Ball Into The Ring with an average CVR value of 0.1, it can be interpreted that the ball into the ring game has high validity, which means the ball into the ring game is safe to use, in accordance with the characteristics and basic competencies of class VII junior high school students.